Adsorption and sustained release of haemoglobin imprinted polysiloxane using a calcium alginate film as a matrix. Issue 34 (15th April 2015) - Zhu, Dunwan; Chen, Zhuo; Zhao, Kongyin; Kan, Bohong; Li, Hui; Zhang, Xinxin; Lin, Beibei; Zhang, Linhua
<x xml:space="preserve">Abstract</x> Schematic representation of the fabrication procedure of the CA film based MIP.